The effect of 2 different distraction-compression models on new bone generation - ÇELEBİLER, ÖZHAN BEKİR; AKDENİZ DOĞAN, ZEYNEP DENİZ (My University, 2012)
To compare the stimulating effect of distraction and 2 different distraction-compression models on maturation of new bone during healing. Thirty adult Sprague-Dawley rats underwent unilateral mandibular osteotomy. The animals were divided into 3 groups. A unidirectional external distraction device was fixed to the mandible. A total of 4 mm of distraction was planned in all groups. After a latency period of 3 days, 0.2 mm of distraction was performed twice a day for 10 days in the distraction group. In the intermittent distraction-compression group, 0.2 mm of distraction was performed twice a day for 3 days, followed by 0.2 mm of compression twice a day for 1 day. In the overdistraction-compression group, 0.2 mm of distraction was performed twice a day for 14 days, followed by 0.2 mm of compression twice a day for 4 days. After a consolidation period of 6 weeks in all groups, animals were killed for macroscopic, microscopic, and radiologic evaluation. Radiologic evaluation proved that more mature bone generation occurred in the groups in which compression was added to distraction. The number of osteoblasts in the intermittent distraction-compression group was significantly higher than that in the distraction group and overdistraction-compression group (P < .001). The highest number of vessels was found in the intermittent distraction-compression group (17.7 ± 6.4) (P < .001). The intermittent distraction- compression model was found to generate greater new bone compared with distraction alone. In clinical applications, to increase the quality of the bone and to shorten the consolidation period, compression can be applied during distraction. © 2012 American Association of Oral and Maxillofacial Surgeons.